Mechanizmy motywacji a wybór strategii uczenia się uczniów szkół gimnazjalnych z i bez specyficznych trudności w uczeniu się - Kucharczyk, Izabella; Dłużniewska, Agnieszka (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The purpose of this article is to present the results of research concern setting of motivated and cognitive strategies in learning goals achieving by students with and without dyslexia in secondary school. The study included 110 students studying in secondary schools in the Mazovian region. The study used questionnaire Goal Orientations and Learning Strategies Survey (GOAL-S) M. Dowson and D.M. McInerney (2004) in the Polish adaptation of A. Dłużniewska and I. Kucharczyk. Detailed analysis of the results indicates the relationship between the kind of motivation and choice of cognitive and metacognitive strategies of learning. The current study allows to extract factors that are important in achieving success in academic achievements of students with and without special educational needs.